Howdy, Stranger!

It looks like you're new here. If you want to get involved, click one of these buttons!

Sign In with Facebook Sign In with Google Sign In with OpenID

Categories

We have migrated to a new platform! Please note that you will need to reset your password to log in (your credentials are still in-tact though). Please contact lee@programmersheaven.com if you have questions.
Welcome to the new platform of Programmer's Heaven! We apologize for the inconvenience caused, if you visited us from a broken link of the previous version. The main reason to move to a new platform is to provide more effective and collaborative experience to you all. Please feel free to experience the new platform and use its exciting features. Contact us for any issue that you need to get clarified. We are more than happy to help you.

Ackermann Function

StebelStebel Posts: 1Member
Hi

I need to put the Ackermann Function in NOT recursive code.

Do you know any idea how to make it iterally ??

The function is defined like that

A(m ; n) =

= n+1 if m=0
= A(m-1 ; 1 ) if (m>0 and n=0)
= A(m-1 ; A(m ; n-1)) if else

Thanks for all the suggetions
Stebel, Poland.

Comments

  • zibadianzibadian Posts: 6,349Member
    : Hi
    :
    : I need to put the Ackermann Function in NOT recursive code.
    :
    : Do you know any idea how to make it iterally ??
    :
    : The function is defined like that
    :
    : A(m ; n) =
    :
    : = n+1 if m=0
    : = A(m-1 ; 1 ) if (m>0 and n=0)
    : = A(m-1 ; A(m ; n-1)) if else
    :
    : Thanks for all the suggetions
    : Stebel, Poland.
    :
    :
    Here is a code, which should result in the pseudocode you gave. I don't know if its correct, but it uses an iterative method of getting the result.
    [code]
    function A(m, n: integer): integer;
    begin
    if m = 0 then
    Result := n + 1
    else if (m > 0) and (n = 0) then
    Result := A(m-1, 1)
    else
    Result := A(m-1, A(m, n-1));
    end;
    [/code]
  • Phat NatPhat Nat Posts: 757Member
    : : Hi
    : :
    : : I need to put the Ackermann Function in NOT recursive code.
    : :
    : : Do you know any idea how to make it iterally ??
    : :
    : : The function is defined like that
    : :
    : : A(m ; n) =
    : :
    : : = n+1 if m=0
    : : = A(m-1 ; 1 ) if (m>0 and n=0)
    : : = A(m-1 ; A(m ; n-1)) if else
    : :
    : : Thanks for all the suggetions
    : : Stebel, Poland.
    : :
    : :
    : Here is a code, which should result in the pseudocode you gave. I don't know if its correct, but it uses an iterative method of getting the result.
    : [code]
    : function A(m, n: integer): integer;
    : begin
    : if m = 0 then
    : Result := n + 1
    : else if (m > 0) and (n = 0) then
    : Result := A(m-1, 1)
    : else
    : Result := A(m-1, A(m, n-1));
    : end;
    : [/code]
    :

    Unfortunately, it's still calling itself here, so it still is recursive. Why not try using [b]While NOT ()[/b] functions with maybe some arrays? It's going to take some time, but there's sure to be a way. My instructor said that you couldn't do the Towers of Hanoi without recursion (so obviously, I took the challenge ;)
    Keep on it. It will work itself out.

    Phat Nat


Sign In or Register to comment.